PERLINDUNGAN HUKUM TERHADAP HAK-HAK PEKERJA PEREMPUAN PADA HIBURAN MALAM - Budimah Budimah (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
The existence of nightclubs today is increasing in number. It is undeniable that nightclubs play an important role in driving the economic sector of some in the country. The development of nightlife venues as a promising business has made many female workers involved because female workers can attract more customers to enter the nightlife venues. Fulfillment of the rights of women workers in nightclubs where the practice is not in accordance with the labor law because most employers have not been able to carry out their obligations such as creating a sense of security in carrying out work and providing shuttle facilities for women workers as mandated in Article 76 of Law Number 13 Year 2003 concerning Manpower Keyword: Women Workers Rights. Legal protection